I. Prijatelj in A. Nowaczyński: informativno-kreativna funkcija prevoda (Wildovi aforizmi prek polščine v slovenščino) / I Prijatelj i A Nowaczyński: informacyjno-kreatywna funkcja przekładu (aforyzmy Wilde’a tłumaczone poprzez polski na słoweński) - Stanovnik, Majda (Przekłady Literatur Słowiańskich, 2016)
(tłum. Agnieszka Bukowczan i Joanna Cieślar) I. Prijatelj and A. Nowaczyński: the informative and the corrective function of translation (Wilde’s aphorisms rendered into Slovene via Polish) The Slavic scholar Ivan Prijatelj (1875—1937), who received his university education in Vienna and was a contemporary and collaborator of the group of Slovene writers known as the »Slovene Modernists« (slovenska moderna), established himself primarily as an influential literary historian. Apart from that, he developed his interests in literature as an essayist and translator, being eager to become familiar with important authors and literary currents, especially modern European ones, and to make them accessible to Slovene readers. He succinctly presented the English writer, who at the time garnered attention in Eastern and in Western Europe, in the journal article Oskar Wilde (1907), which is a translation of Wilde’s aphorisms on art and on criticism. They were translated into Slovene from Polish, on the basis of Oskar Wilde. Studjum. Aforyzmy. Nowele, a book by Adolf Nowaczyński (1906), in which Wilde is dealt with in a more extensive and multi‑faceted manner. Prijatelj’s version, which is thematically homogeneous, is the only one among his translations that is not based directly on the source text. It does not always follow Nowaczyński’s translation, but is consistent with the poetics of translation sketched out by Prijatelj in the introductory chapter to his study on Pushkin in Slovene translations (1901). The study presupposes that for the literature of a small nation such as Slovenia, translation is indispensable in as far as it enables that literature to become connected to other national literatures; in actual fact, translations are considered as a means of informing and educating target readers as well as of correcting local literary standards. In order to perform these functions in a satisfactory way, a translation must preserve the original’s authenticity, while at the same time adapting to the target culture and naturally integrating into it. Accordingly, a translated text does not only bear a mark of the author’s creative genius, but, to an extent, also of that of the translator. Some minor shifts with respect to the English original are observable in Prijatelj’s and Nowaczyński’s translations, which in some points differ also from each other, and remain within the recommended middle way, which makes it possible for the translator to take into account the author’s intentions, while allowing himself the necessary freedom, so as to produce an effective and convincing target text. Key words: translation function, aphorism, I. Prijatelj, O. Wilde, A. Nowaczyński